Pengaruh Program Kampus Mengajar Terhadap Upaya Persiapan Menjadi Guru Profesional Pada Mahasiswa FKIP Unidayan - Widia R., Sri Indah; Lestari, Dian (Program Studi Pendidikan Matematika, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Dayanu Ikhsanuddin, 2024)
The aim of this research is to find out the influence of Kampus Mengajar program on preparation efforts to become professional teachers for students of FKIP Unidayan. This is a quantitative research by applying the Ex-post Facto method. The research population is limited to participants of Kampus Mengajar on generation VI with a total of 33 students. In this research, the sample from participants of Kampus Mengajar on generation VI Faculty of Teacher Training and Education with a total of 27 students. The instrument used was a questionnaire about Kampus Mengajar programs and the preparation efforts to become professional teachers. This data was analyzed using simple linear regression analysis. The results of this research can be concluded that, there is an influence of the Kampus Mengajar program on the preparation efforts to become professional teachers for students of FKIP Unidayan.